Systematic literature review: The adaptation of distance learning process during the COVID-19 pandemic using virtual educational spaces in metaverse - Onggirawan, Cindy Amanda; Kho, Jocelyn Michelle; Kartiwa, Arya Putra; Anderies; Gunawan, Alexander A S (Procedia computer science, 2023)
Virtual education has started to grab interest since technology emerges in everything in our life. Metaverse is one of the technologies that has been conceived since the late 90s and is currently being renewed and renovated to suit current changes. Yet, many teachers and students still do not know how to utilize Metaverse to create a new atmosphere in the learning process. Therefore, this study aims to show the results of using Metaverse in the form of virtual space in the educational field and how teachers and students respond to the process. In this study, the authors would like to conduct a Systematic Literature Review (SLR) on the advantages and disadvantages of virtual educational spaces in Metaverse based on many previous studies related to this topic. Survey results conducted by previous studies show that students mostly enjoy using Metaverse as their learning method and can comprehend several lessons better when using Metaverse than traditional learning— textbook-based and face-to-face learning. Unfortunately, only several studies focus on finding preferred subjects to teach using the Metaverse and for which educational level this method suits best. In general, the authors conclude that Metaverse has excellent potential in the future to be explored profoundly in the education field due to the development of skills in the use of technology and a significant increase in student practice scores. However, the guidance of teachers and parents is still needed so that students can avoid the disadvantages.